Experimental investigations on the performance and noise characteristics of a forward-curved fan with the stepped tongue. (November 2019) - Yang, Hui; Yu, Peiquan; Xu, Jun; Ying, Cunlie; Cao, Wenbing; Wang, Yingdong; Zhu, Zuchao; Wei, Yikun
This work presents an experimental study to investigate the influence of step volute tongue on aerodynamic performance and aeroacoustic behavior of a forward-curved fan. The noise characteristics are analyzed and controlled based on measured acoustic pressures for various stepped tongues; meanwhile, fan performance is detected and optimized. The design parameters of the stepped tongues are presented to provide significant physical insight into increasing the static pressure as well as the efficiency of static pressure and reducing the fan noise generation. The comparison of the test results indicates that the improved static pressure and its efficiency of the HLHL model have increased by 15.67 Pa and 3.57%, respectively, by comparing with those of the baseline model. At 740 m 3 /h, a great correlation between different arrays of stepped tongue and the noise generation was observed. The tonal noise level of the HLHL model is a better optimization scheme because it decreases as much as 1.2 dB for the noise generation of forward-curved fan. In particular, it is found that some stepped tongues of the volute tongue achieved the goal of reducing noise generation and improving the performance of fan by experimental measurement at the same time.